Development and Implementation of Diabetes Care by a Community Network Based on a Chronic Care Model - Kanniyaporn Boocha; Chanuttha Ploylearmsang (SAGE Publishing, 2023)
Introduction: This participatory action research was conducted by the collaborative health-related team in a district, in Thailand. The community network jointly developed a care model for diabetic patients in primary care using the Chronic Care Model (CCM) and evaluated the effectiveness of implemented model. Methods: Data was collected between October 2021 and March 2022 and involved 2 groups: 1) a community network of 25 people including representatives of the community hospital, primary care hospital, Sub-district administrative organization, community leaders, community representatives, representatives of diabetic patients, and representatives of caregivers of diabetic patients, and 2) 41 people with type 2 diabetes and 41 of their family caregivers. The research was conducted in 4 stages: planning, action, observation, and reflection. Results: Both quantitative and qualitative data were collected, and the overall average knowledge scores of diabetic patients, family caregivers, and community representatives significantly increased from before (6.07 ± 2.11, 7.07 ± 1.98, P  = .024, 5.74 ± 1.88, 7.37 ± 2.25, P  < .001, 7.47 ± 2.44, 8.99 ± 1.72, P  = .010) respectively. For satisfaction, diabetic patients were most satisfied with family caregiver support, while the community network representatives were most satisfied with their participation in planning a model for diabetic patients in primary care. After model implementation, the blood sugar-controlled patients (HbA1c < 7 mg%) significantly increased (0 and 9.76%, P  = .045), although the fasting blood sugar (FBS) of diabetic patients did not improve. Conclusion: The development and implementation of diabetes care based on CCM, promoted community participation and involvement in diabetes care. This model mainly affected diabetic patients who could control their HbA1c level and the satisfaction of the community network.